(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article analyzes the linguistic features of the ghazals given in Amiri’s "Devon". The stylistic, linguistic, lexical-semantic features of Devonian Arabic acquisitions are studied.